The anglo-american world in TEFL in portuguese secondary education - Feneja, Fernanda Luísa da Silva, 1964- (2014)
Anglo-American culture pervades the Portuguese national syllabus for the teaching of English as a foreign language throughout the seven or eight years of its obligatory school study, ranging from very simple references to common, accepted, often stereotyped behaviors or traditions, in the early years, to far more complex issues in the upper levels, such as, to name but two, the Civil Rights Movement in the US or multiculturalism as a trait of British society. Primarily acknowledging the bond between language and culture, this essay aims to reflect on the role of Anglo-American culture and history in the broader context of the English syllabus at secondary level in Portuguese schools. Furthermore, it takes into account the current approaches that reinforce the contribution of Anglo-American studies to the achievement of the aims informing the rationale of the official programmes, in particular, those related to crosscultural awareness, citizenship and tolerance. The contribution of the literary text to the teaching of English as a second language, namely as a tool for looking into Anglo-American culture and society, is also considered. The discussion of such issues might hopefully contribute to the debate over the current impact of Anglo-American studies in Portugal and the possibilities and paths lying ahead.